Contribution of genetic, epigenetic and transcriptomic differences to twin discordance in multiple sclerosis. - Handunnetthi, L; Handel, A; Ramagopalan, S (2010)
Evaluation of: Baranzini SE, Mudge J, van Velkinburgh JC et al. Genome, epigenome and RNA sequences of monozygotic twins discordant for multiple sclerosis. Nature 464, 1351-1356 (2010). Multiple sclerosis (MS) is a chronic inflammatory disease of the CNS. Genetically identical (monozygotic) twins have a concordance rate for MS of approximately 30%, lending support to the notion that the disease has a complex etiology, developing as a result of genetic and environmental factors and their interactions. However, recent studies have highlighted the fact that monozygotic twins might not actually be genetically identical. In an effort to see if this can explain MS twin discordance, Baranzini and colleagues sequenced the genome from a pair of monozygotic twins discordant for MS, and also examined DNA methylation and gene expression across the genome in this twin pair and an additional two more twin pairs. No consistent differences in DNA sequence, DNA methylation or gene expression were found. Here we put these findings into context and discuss their significance.